Nano/micro-structured silicon@carbon composite with buffer void as anode material for lithium ion battery. Issue 1 (January 2016) - Feng, Xuejiao; Cui, Hongmin; Miao, Rongrong; Yan, Nanfu; Ding, Tengda; Xiao, Zhengqiang
Abstract: A novel nano/micro-structured pSi@C composite with buffer void was successfully synthesized via a simple and scalable process with combination of the calcination, spray drying, carbonization and HF etching. The obtained pSi@C composite with this particular structure exhibits high reversible capacity of ca. 2200 mA h g −1 and excellent cycling stability with 90.3% capacity retention after 300 cycles, which benefits from its void spaces between silicon and carbon layer and highly conductive carbon-layer. The simple and scalable synthesis technique and good electrochemical performance of this nano/micro-structured pSi@C composite make it a promising candidate for large capacity lithium ion battery anode material.